THE EXISTENCE OF TRADITIONAL BIRTH ATTENDANTS (DUKUN PARAJI) IN THE PRACTICE OF BIRTH ASSISTANCE SERVICES IN BOGOR REGENCY: EKSISTENSI DUKUN PARAJI DALAM PRAKTIK PERTOLONGAN LAYANAN PERSALINAN DI KABUPATEN BOGOR - Trisasmita, Laksmi (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2024)
Introduction: The role of traditional birth attendants, known as